Safety evaluation of the food enzyme protein‐glutamine γ‐glutamyltransferase from the non‐genetically modified Streptomyces mobaraensis strain AE‐BTG - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme protein‐glutamine γ‐glutamyltransferase (protein‐glutamine: amine γ‐glutamyltransferase; EC 2.3.2.13) is produced with the non‐genetically modified S. mobaraensis strain AE‐BTG by AJINOMOTO EUROPE SAS. The food enzyme was free from viable cells of the production organism. It is intended to be used in nine food manufacturing processes. Dietary exposure to the food enzyme–total organic solids (TOS) was estimated to be up to 0.398 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 538 mg TOS/kg bw per day which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 1351. A search for homology of the amino acid sequence of the food enzyme to known allergens was made and no match was found. Known sources of food allergens were used in the food enzyme manufacturing process, and the Panel considered that the risk of allergic reactions upon dietary exposure to this food enzyme cannot be excluded. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.